Museums and anthropology in the age of engagement - Kreps, Christina F. (Christina Faye) 1956- (New York, NY Routledge, an imprint of the Taylor & Francis Group, 2020)
"Museums and Anthropology in the Age of Engagement considers changes that have been taking place in museum anthropology as it has been responding to pressures to be more socially relevant, useful, and accountable to diverse communities. Based on the author's own research and applied work over the past 30 years, the book gives examples of the wide-ranging work being carried out today in museum anthropology as both an academic, scholarly field and variety of applied, public anthropology. While it examines major trends that characterize our current "age of engagement," the book also critically examines the public role of museums and anthropology in colonial and postcolonial contexts, namely in the US, the Netherlands, and Indonesia. Throughout the book, Kreps questions what purposes and interests museums and anthropology serve in these different times and places. Museums and Anthropology in the Age of Engagement is a valuable resource for readers interested in an historical and comparative study of museums and anthropology, and the forms engagement has taken. It should be especially useful to students and instructors looking for a text that provides in one volume a history of museum anthropology and methods for doing critical, reflexive museum ethnography and collaborative work"--Provided by publisher.
Introduction: museums and anthropology in the age of engagement -- Mapping contemporary anthropology -- Museum and applied anthropology: shared histories and trajectories -- Museums and anthropology in the Netherlands: Colonial and Postcolonial narratives -- "Museum frictions" in Colonial and Postcolonial Indonesia -- International collaboration and the values of culture and heritage -- Doing museum anthropology "at home."
Includes bibliographical references and index.
Keywords: Anthropological museums and collections -- United States; Anthropological museums and collections -- Netherlands; Anthropological museums and collections -- Indonesia; Postcolonialism -- United States; Postcolonialism -- Netherlands; Postcolonialism -- Indonesia; Museums -- Social aspects -- United States; Museums -- Social aspects -- Netherlands; Museums -- Social aspects -- Indonesia